2015
DOI: 10.3389/fgene.2015.00139
|View full text |Cite
|
Sign up to set email alerts
|

Transposon insertion mapping with PIMMS – Pragmatic Insertional Mutation Mapping System

Abstract: The PIMMS (Pragmatic Insertional Mutation Mapping System) pipeline has been developed for simple conditionally essential genome discovery experiments in bacteria. Capable of using raw sequence data files alongside a FASTA sequence of the reference genome and GFF file, PIMMS will generate a tabulated output of each coding sequence with corresponding mapped insertions accompanied with normalized results enabling streamlined analysis. This allows for a quick assay of the genome to identify conditionally essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…Sequence data was analyzed and mapped back to the original genome using the PIMMS bioinformatic pipeline (Blanchard et al, 2015). Comparative analysis indicated that the number of sequence reads that included 23 bp from either terminus of the insertion sequence (Matched Reads; Table 1 ) was similar for the EcoR1 and HindIII digested samples (62.3% and 62.9%, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Sequence data was analyzed and mapped back to the original genome using the PIMMS bioinformatic pipeline (Blanchard et al, 2015). Comparative analysis indicated that the number of sequence reads that included 23 bp from either terminus of the insertion sequence (Matched Reads; Table 1 ) was similar for the EcoR1 and HindIII digested samples (62.3% and 62.9%, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…A bioinformatic pipeline (Blanchard et al, 2015) was used to map the sequence directly adjacent to the IS S1 terminus to the S. uberis reference genome (accession number AM946015; Ward et al, 2001). This revealed that between 39 and 25% of the matched reads mapped unambiguously to the source genome.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations